DETERMINATION OF BIOACTIVE COMPOUNDS AND BIOLOGICAL PROPERTIES OF TAMARINDUS INDICA STEM BARK EXTRACT AGAINST SELECTED MICROBES - ABOKO, JAMES; ANABIA, MARGARET; ACHEAMPONG, CHARLES (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: The present study determines the bioactive constituents in the stem bark of Tamarindus indica and also assesses its biological properties against Staphylococcus aureus and Pseudomonas aeruginosa in vitro. Methods: The clinical isolates were collected from wounds of patients and cultivated in a nutrient broth. The extract of stem bark of T. indica was added to the bacteria in Muller Hinton ager to test its biological activity. Results: Crude extracts of T. indica showed potency against S. aureus with the highest zone of inhibition of 19.00 ± 0.60 mm at 200 mg/ml concentration of the extract. The extract showed potency against P. aeruginosa at varying concentrations with a zone of inhibition between 13.5 ± 0.20 mm and 6.25 ± 0.45 mm. However, the extracts of T. indica recorded a minimum inhibitory concentration (MIC) value of 6.25 mg/ml and an minimum bactericidal concentration value of 25 mg/ml against P. aeruginosa and also recorded a MIC value of 3.13 mg/ml against S. aureus. The preliminary analysis of bioactive compounds of the crude extract of T. indica showed that it has a wide range of phytochemical constituents including saponins, alkaloids, flavonoids, tannins, and anthraquinones. Conclusion: The results suggested that the extract of stem bark of T. indica has the potential of being the best alternative antimicrobial agent use to cure infectious diseases caused by S. aureus and P. aeruginosa.